Motherhood Health Penalty: Impact of Fertility on Physical and Mental Health of Chinese Women of Childbearing Age - Yao Jiang; Fan Yang (Frontiers Media S.A., 2022)
BackgroundThe negative consequences of childbearing on mothers are called the motherhood penalty, and it manifests in the aspects of women's physical and mental health. In May 2021, China relaxed its birth policy that allowed a married couple to have three children. It gives women the opportunity to have more children, but also may increase more risks to mothers' physical and mental health.ObjectivesThe objectives of this study were to clarify the relationships between the fertility and the physical/mental health of women of childbearing age and empirically confirm the existence of the motherhood health penalty in China.Materials and MethodsUsing a nationally representative dataset from the China Labor-force Dynamics Survey 2018, we examined the effects of fertility on the physical and mental health of Chinese women of childbearing age. Physical health was self-rated, and mental health was assessed according to the Center for Epidemiological Studies Depression scale. The instrumental variable approach and the models of inverse probability of treatment weighting of propensity scores and regression adjustment were employed to overcome the endogeneity between fertility and health of women.ResultsThe empirical results showed that the total number of births had significant adverse impacts on the physical and mental health of women of childbearing age, which empirically demonstrated the existence of the motherhood health penalty in China. The results of heterogeneity analysis indicated that the physical and mental health of the rural women was more easily affected by childbearing compared with that of the urban samples. In a mechanism analysis, the pathways of income and the multiple roles played by mothers were found to mediate the impacts of the total number of births on the physical and mental health of women. The robustness checks showed that the results of this study were robust.ConclusionsThe findings of this study extend the motherhood penalty to the health domain, and they have important implications for improving healthcare policy for women of childbearing age in China and other countries and regions and promoting gender equality in the healthcare field.